(untitled) (Journal of Dhaka Medical College, 2010)
Aim: To find out an effective drug for the treatment of allergic conjunctivitis and to compare the efficacy of Sodium chromoglycate ophthalmic solution and Olopatadine Hydrochloride 0.1% ophthalmic solution in the treatment of allergic conjunctivitis. Materials and methods: This randomized double blinded study was conducted in National Institute of Ophthalmology and Hospital, Sher-E-BangIa Nagar, Dhaka, from January, 2005 to May, 2009. 100 Patients with ocular allergies attending OPD of NIO&H were included. Each of the patient was randomly included in either of the following two groups by simple lottery method; Group A: 50 Patients receiving olopatadine hydrochloride 0.1% eye drops and Group B: 50 Patients receiving sodium chromoglycate 2% eye drops. Itching score, Redness score, Discharge score, Evaluator’s score - baseline and after 21 days of treatment with olopatadine and sodium chromoglycate 2% ophthalmic solution were evaluated following Aguilar (2000). For the relieving of symptoms and signs olopatadine was found to be superior over sodium chromoglycate 2% but the difference was not statistically significant. Conclusion: This clinical study concludes that the relieving of symptoms and signs olopatadine was found to be superior over sodium chromoglycate 2% but the difference was not statistically significant. DOI: 10.3329/jdmc.v18i2.6274 J Dhaka Med Coll. 2009; 18(2) : 136-139